(untitled) (PANGEEA, 2025)
This paper aims to bring to attention professional ethical issues in the practice of social workers, exploring fundamental values, codes of ethics, ethical challenges, in the literature. The values and ethics of social assistance are an integral part of the practice of social assistance and higher education. An important role in the social worker profession is played by moral values, such as equity, respect for human dignity, respect for human self-determination, social justice, human solidarity, respect and care for others.